How do you combine like terms in the (9y^{2} - 2y - 4) + ( - 6y^{2} + y + 7)?

1 Answer
Jul 3, 2018

3y^2-y+3

Explanation:

First, put like terms next to each other for easy solving.
(9y^2-2y-4)+(-6y^2+y+7)
=(color(red)(9y^2-6y^2))+(color(blue)(-2y+y))+(color(orange)(-4+7))
Then, combine the like terms.
=(color(red)(9y^2-6y^2))+(color(blue)(-2y+y))+(color(orange)(-4+7))
=color(red)(3y^2)+color(blue)(-y)+color(orange)(3)
Change any redundant symbols so the expression makes sense.
=color(red)(3y^2)+color(blue)(-y)+color(orange)(3)
=color(red)(3y^2)color(blue)(-y)color(orange)(+3)